Associations between Weight Status and Situational Motivation toward Fitness Testing in Physical Education: The Mediator Role of Physical Fitness - Grao-Cruces, Alberto (Int J Environ Res Public Health, 2020)
Background: This article examines the differences in situational motivation toward fitness testing in physical education classes between non-overweight and overweight students, as well as the mediator effect of objective and perceived physical fitness on the relationship between weight status and motivation toward fitness testing. Methods: A total of 534 adolescents (298 boys, 55.80%) participated in the study. Perceived physical fitness and situational motivation toward fitness testing were measured through questionnaires, whereas weight status and physical fitness were objectively measured. Results: Overweight students had lower intrinsic motivation (p < 0.001), and higher external regulation (p < 0.01) and amotivation (p < 0.05) during fitness testing in a physical education class than their non-overweight peers. The influence of being overweight on motivation regulations toward fitness testing was mediated by objective physical fitness level for intrinsic motivation (B = −0.140), external regulation (B = 0.104) and amotivation (B = 0.146). Perceived physical fitness was also used as a second mediator between weight status and intrinsic motivation (B = −0.117). Conclusions: Strategies to improve objective and perceived physical fitness in overweight students are necessary to increase self-determined motivation during fitness testing in physical education lesson.